Enhancing Teacher Competency in Interactive Video Development for Speech-Delayed Children through Guided Project-Based Learning Training - Kartikasari, Diastuti; Ishartiwi, Ishartiwi (Journal of Innovation and Research in Primary Education, 2025)
Speech delay affects 5-10% of preschool children, requiring specialized educational interventions. However, kindergarten teachers often lack competencies in creating appropriate interactive video media for these children. This study investigated the effectiveness of guided Project-Based Learning (PjBL) training in enhancing teacher capabilities for developing interactive video media specifically designed for speech-delayed children. An action research design using the Kemmis and McTaggart model was implemented over two cycles at AN-NUR Kindergarten, East Kalimantan. Ten kindergarten teachers participated in guided PjBL training focusing on interactive video creation using Canva application. Data collection employed pre-test/post-test assessments, structured observations, interviews, and product documentation. Cycle II incorporated expert collaboration and artificial intelligence features to enhance training effectiveness. Teacher competency showed substantial improvement from baseline scores of 46.5 to final scores of 83.5, representing a 79.6% overall increase. Cycle I achieved 32.3% improvement (46.5 to 61.5), while Cycle II demonstrated 35.7% enhancement (61.5 to 83.5). Design appropriateness improved by 183% and audio integration by 140% in Cycle II. Nine participants (90%) achieved competency thresholds by study completion, compared to 50% in Cycle I. Qualitative observations revealed enhanced confidence, collaboration, and creative expression among participants. Guided PjBL training effectively enhances teacher competencies for creating interactive video media for speech-delayed children. The structured, collaborative approach combining theoretical knowledge with hands-on practice proves superior to traditional training methods. The integration of expert collaboration and advanced technological features significantly accelerates competency development. These findings support the implementation of PjBL-based professional development programs for specialized educational populations.